Prior accounting knowledge of first-year students at two South African universities: Contributing factor to academic performance or not? - Papageorgiou, E.; Carpenter, R. (South African Journal of Higher Education, 2020)
Factors that influence students’ academic performance are important for higher education institutions, students and professional bodies. This study focuses on the prior accounting knowledge of students entering higher education, one of the factors that could influence students’ success. The reasons for revisiting this factor are firstly, admission requirements for students applying for the Bachelor of Commerce (BCom) in Accounting degree are different among South African universities regarding Accounting as a pre-requisite school subject; secondly, Grade 12 subjects have changed significantly with the introduction of the National Senior Certificate (NSC) examination in 2008; and lastly, comparing students’ prior accounting knowledge as a contributing factor or not of international studies with South African studies. The purpose of this study was to investigate the effect on first-year Accounting students’ academic performance whether they had or did not have Accounting as a school subject for students enrolled for an Accounting degree at two South African universities. The research method used a quantitative methodology. The findings of the study offer a better understanding of and a greater sensitivity for students’ prior knowledge which might influence their academic performance. The value of the study is an important contribution to the consideration of admission requirements for students applying for an Accounting degree at South African universities.